Energy Consumption and Economic Growth: The Evidence from India - Sultan, Zafar Ahmad; Alkhateeb, Tarek Tawfik Yousef (International Journal of Energy Economics and Policy, 2019)
The oil price shock of the 1970s and its disruptive impact on the economic activities all over the world dragged the attention of researchers to study the interaction between energy and real output. However, no conclusive evidence could be submitted about the direction of causality between the two. The present study has been an attempt to understand such relationship in the case of India. The paper has used the data from 1971 to 2014 and has found long run stable relationship between energy use and real output. The study also reveals that in the short run, there is unidirectional relationship between the two and energy Granger causes economic activities in India. In the long run, we find bidirectional relationship between energy and economic prosperity of India. Keywords: Oil Consumption, Economic Growth, India. JEL Classifications: E20, E22, E31. DOI: https://doi.org/10.32479/ijeep.8030